2006
DOI: 10.1055/s-2006-950282
|View full text |Cite
|
Sign up to set email alerts
|

A Remarkable HBF4-SiO2-Catalyzed Synthesis of Acylals from Aldehydes under Solvent-Free Conditions

Abstract: HBF 4 -SiO 2 has been found to be an outstanding catalyst for the protection of carbonyl compounds as acylals under entirely solvent-free conditions. Some of the major advantages of this procedure are high yields, ease of operation, high chemoselectivity, high atom efficiency, and compatibility with other protecting groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…HBF 4 is a common acid in academic and industrial laboratories that has found diverse applications in synthesis, either as a reagent (nucleophilic fluorination,9 synthesis of vinylidene–metal complexes10), or catalyst (amidation of olefins,11 Biginelli reaction,12 acylation of aldehydes13). In particular, the Friedel–Crafts alkylation of benzylic alcohols in the presence of an excess of HBF 4 · OEt 2 solution at –78 °C has been reported 14.…”
Section: Introductionmentioning
confidence: 99%
“…HBF 4 is a common acid in academic and industrial laboratories that has found diverse applications in synthesis, either as a reagent (nucleophilic fluorination,9 synthesis of vinylidene–metal complexes10), or catalyst (amidation of olefins,11 Biginelli reaction,12 acylation of aldehydes13). In particular, the Friedel–Crafts alkylation of benzylic alcohols in the presence of an excess of HBF 4 · OEt 2 solution at –78 °C has been reported 14.…”
Section: Introductionmentioning
confidence: 99%
“…HBF 4 is a benign fluoride source known as a versatile acid owing to its diverse applications in both industrial and academic synthesis . HBF 4 can be used as a catalyst for various reactions, including the acylation of aldehydes, Friedel–Crafts alkylation of 1‐aryl‐1‐alkanols, amidation of olefins, and the Bignelli reaction, and as a reagent in vinylidene metal complex synthesis and nucleophilic fluorination. Despite the notorious inertness and stability of tetrafluoroborates, HBF 4 is interestingly an effective alternative for fluorination …”
Section: Halogenation Of Diazo Compoundsmentioning
confidence: 99%
“…13,14 In recent years, the use of catalysts immobilized on solid supports has received considerable attention. [15][16][17][18][19] Such catalysts not only simplify the purification process but also help in preventing the release of reaction residues into the environment. Thus, the solvent-less condition along with supported catalyst provides a protocol for achieving environment friendly organic synthesis.…”
Section: Introductionmentioning
confidence: 99%